Transcription of repetitive sequences on Xenopus lampbrush chromosomes. - Jamrich, M (1983)
We reinvestigated the lampbrush chromosomes of Xenopus laevis and found them well suited for the study or transcription by in situ hybridization to nascent RNA transcripts. Using this technique, we analyzed the transcription of three repetitive sequences that do not show any sequence homology and that differ in their degree of interspersion. We found that they are located on different parts of the chromosomes: two are clustered, one is interspersed. All three of these sequences are transcribed at the lampbrush chromosome stage and transcripts from both strands of each sequence can be detected. The amount of transcription is apparently not proportional to the number of copies of the repetitive sequence at a given chromosomal locus, suggesting that other sequences are involved in the regulation of their transcription.